An intuitive method to improve the estimation of output gaps - Wollfram Wilde; Joscha Beckmann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Standard procedures for output gap estimates, such as the Hodrick-Prescott Filter or the Production Function Method, suffer from the sample phase shift issue at the end of the sample. This often provides unstable and unreliable estimates for the current output gap. However the current estimate of output gaps is the most relevant one for monetary and fiscal policymakers. The result from time series filters lack an economic founding and tend to produce economic implausible results for the output gap. This paper introduces and evaluates a new method which is able to reduce the uncertainty of output gaps at the end of a sample while allowing for an economic interpretation of the obtained estimate. Our estimates for 12 economies show that we are able to outperform the popular production function methodology (PF) when nowcasting the current output gap.
Keywords: E52; E58; 330; Output Gap; Policy Evaluation